Radio Galaxy Zoo: A Search for hybrid morphology radio galaxies - Kapiñska, A.; Terentev, I.; Terentev, W.; Shabala, S.; Shabala, A.; Rudnick, L.; Storer, L.; Banfield, J.; Willett, K.; Willett, F.; Willett, C.; Willett, A.; et al. (Institute of Physics Publishing, 2017)
Hybrid morphology radio sources (HyMoRS) are a rare type of radio galaxy that display different Fanaroff-Riley classes on opposite sides of their nuclei. To enhance the statistical analysis of HyMoRS, we embarked on a largescale search of these sources within the international citizen science project, Radio Galaxy Zoo (RGZ). Here, we present 25 new candidate hybrid morphology radio galaxies. Our selected candidates are moderate power radio galaxies (L median 4.7×10 24 WHz -1 sr -1 ) at redshifts 0.14 > z > 1.0. Hosts of nine candidates have spectroscopic observations, of which six are classified as quasars, one as high- A nd two as low-excitation galaxies. Two candidate HyMoRS are giant ( > 1 Mpc) radio galaxies, one resides at the center of a galaxy cluster, and one is hosted by a rare green bean galaxy. Although the origin of the hybrid morphology radio galaxies is still unclear, this type of radio source starts depicting itself as a rather diverse class. We discuss hybrid radio morphology formation in terms of the radio source environment (nurture) and intrinsically occurring phenomena (nature; activity cessation and amplification), showing that these peculiar radio galaxies can be formed by both mechanisms. While high angular resolution follow-up observations are still necessary to confirm our candidates, we demonstrate the efficacy of the RGZ in the pre-selection of these sources from all-sky radio surveys, and report the reliability of citizen scientists in identifying and classifying complex radio sources.